ОЦІНКА ВПЛИВУ СУМАРНОЇ ВЕКТОРНОЇ ПОХИБКИ ТА ПРОБЛЕМ СИНХРОНІЗАЦІЇ ЧАСУ НА ФУНКЦІОНУВАННЯ ШИРОКОМАСШТАБНИХ СИСТЕМ МОНІТОРИНГУ ЕНЕРГОСИСТЕМ - Стогній, Б.С.; Сподинський, О.В. (Інститут електродинаміки Національної академії наук України, 2026)
In this paper, the total vector error (TVE) of the estimated phasor is assessed for different local area network (LAN) access environments defined in Standard IEEE C37.118.1-2011, and the critical role of accurate time synchronization for synchrophasor technology is investigated. Phasors synchronized to absolute time constitute the foundation of phasor measurement units (PMUs), which are widely used for power system monitoring. The TVE assessment is performed for three local network models – CSMA/CD, CSMA/AMP, and switched Ethernet – taking into account standardized network bandwidth (BW) values of 0.1, 1, and 10 Gbit/s in accordance with Standard IEC 61850-9-2:2011, as well as the number of network nodes. A methodology for evaluating the impact of internal and external PMU measurement errors on the performance of critical wide-area monitoring system (WAMS) applications is analyzed, including disturbance localization, oscillation detection, and dynamic line rating (DLR). The analysis results demonstrate that TVE is highly sensitive to the type of local area network and the number of nodes, while the accuracy of time synchronization remains a significant challenge affecting the reliability of WAMS applications.  Ref. 10.